2017
DOI: 10.3389/fmicb.2017.02538
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of the Endophytic Bacterium Pseudomonas fluorescens Sasm05 and IAA on the Plant Growth and Cadmium Uptake of Sedum alfredii Hance

Abstract: Endophytic bacteria have received attention for their ability to promote plant growth and enhance phytoremediation, which may be attributed to their ability to produce indole-3-acetic acid (IAA). As a signal molecular, IAA plays a key role on the interaction of plant and its endomicrobes. However, the different effects that endophytic bacteria and IAA may have on plant growth and heavy metal uptake is not clear. In this study, the endophytic bacterium Pseudomonas fluorescens Sasm05 was isolated from the stem o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 76 publications
2
33
0
1
Order By: Relevance
“…Most data currently available on lipid peroxidation in response to Cd stress concern adult plants (Romero-Puertas et al, 2019); less is known about seedlings germinated and grown under Cd treatment. Thus, lipid peroxidation has been observed to increase in Cd-treated 6-day-old Arabidopsis seedlings (Chen et al, 2017), which is in line with our findings.…”
Section: Damage To Cd-treated Seedlingssupporting
confidence: 92%
See 1 more Smart Citation
“…Most data currently available on lipid peroxidation in response to Cd stress concern adult plants (Romero-Puertas et al, 2019); less is known about seedlings germinated and grown under Cd treatment. Thus, lipid peroxidation has been observed to increase in Cd-treated 6-day-old Arabidopsis seedlings (Chen et al, 2017), which is in line with our findings.…”
Section: Damage To Cd-treated Seedlingssupporting
confidence: 92%
“…Oxidative stress is one of the primary effects of Cd treatment in both adult plants and seedlings (Chen et al, 2017;Gupta et al, 2017;Ortega-Galisteo et al, 2012). We have used the whole seedlings to analyse oxidative markers, as roots and leaves at the seedling stage are still too small to be analysed separately.…”
Section: Damage To Cd-treated Seedlingsmentioning
confidence: 99%
“…Several studies documented that endophytic bacteria associated with plant growth promotion, such as Bacillus licheniformis, enhanced copper (Cu), zinc (Zn), chromium (Cr), Cd and Pb accumulation and distribution in plants grown in heavy metal-contaminated soil, which led to reduced levels of toxic metals in the soil (Brunetti et al 2012). The endophytic bacterium Pseudomonas fluorescens Sasm05 promoted Sedum alfredii Hance growth and enhanced Cd accumulation in response to Cd stress [13].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous reports have demonstrated that the application of hemin as a potent biostimulator mitigates metal-induced oxidative stress by enhancing the stress tolerance of plants 1,10 . For example, the application of exogenous hemin ameliorates Al and Cd toxicity in Medicago sativa L. 11,12 , induces ammonium tolerance in Oryza sativa L. 10 and enhances salinity stress adaptations in Triticum aestivum L. 13 .…”
mentioning
confidence: 99%
“…To the best of our knowledge, the influence of hemin on the cadmium resilience and removal potential of V. radiata has not yet been evaluated. Therefore, the aims of the present work were (1) to investigate the effect of exogenous hemin on the biomass production and chlorophyll content of V. radiata; (2) to analyse the mechanism by which hemin affects Cd tolerance of V. radiata; and (3) to verify the influence of exogenous hemin in improving the Cd phytoremediation efficiency of V. radiata.…”
mentioning
confidence: 99%